2009
DOI: 10.1002/ls.89
|View full text |Cite
|
Sign up to set email alerts
|

Complex wear measurement on thin coatings by the cratering method

Abstract: Ball cratering and rotating wheel tests are useful techniques for abrasive wear resistance evaluation of thin coatings. Nevertheless, such techniques involve significant experimental errors, coming from equipment deficiencies and changes in wear response depending on test parameters. In case of rotating wheel test, common instrumental errors are: geometry-induced errors (curved or non-horizontal sample surface), alignment errors (misalignment between ball/wheel rotation axis and sample stage) and optical measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The possible source of errors in rotating wheel abrasive wear tests for thin coatings, such as crater dimensions detection and equipment deficiencies, are investigated in reference [48]. It is found that rotating axes misalignment and sample slope lead to considerable errors in volume calculations and a misestimation in wear coefficients that can be corrected by using some expressions obtained.…”
Section: Coatingsmentioning
confidence: 99%
“…The possible source of errors in rotating wheel abrasive wear tests for thin coatings, such as crater dimensions detection and equipment deficiencies, are investigated in reference [48]. It is found that rotating axes misalignment and sample slope lead to considerable errors in volume calculations and a misestimation in wear coefficients that can be corrected by using some expressions obtained.…”
Section: Coatingsmentioning
confidence: 99%